2016
DOI: 10.1186/s12884-016-0813-3
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and maternal outcomes following midtrimester preterm premature rupture of the membranes: a retrospective cohort study

Abstract: BackgroundPreterm premature rupture of membranes (PPROM) complicates 1 % of all pregnancies and occurs in one third of all preterm deliveries. Midtrimester PPROM is often followed by spontaneous miscarriage and elective termination of ongoing pregnancies is offered in many countries. The aim of this retrospective descriptive cohort study was to investigate the natural history of midtrimester PPROM in a jurisdiction where termination of pregnancy in the absence of maternal compromise is unavailable.MethodsCases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 15 publications
7
61
3
1
Order By: Relevance
“…Linehan et al analyzed the neonatal and maternal outcome in women after PPROM, diagnosed between 14 and 23 + 6 weeks' gestation: only 23% of infants were born alive and the overall mortality rate was 95% [88][89][90]. In this study chorioamnionitis was found in 69% and 12% patients developed post-partum hemorrhage [88].…”
Section: Maternal and Neonatal Outcomesmentioning
confidence: 62%
“…Linehan et al analyzed the neonatal and maternal outcome in women after PPROM, diagnosed between 14 and 23 + 6 weeks' gestation: only 23% of infants were born alive and the overall mortality rate was 95% [88][89][90]. In this study chorioamnionitis was found in 69% and 12% patients developed post-partum hemorrhage [88].…”
Section: Maternal and Neonatal Outcomesmentioning
confidence: 62%
“…Out of 44667 deliveries, 42 cases were selected during the five-year study. The prevalence of PPROM in the second trimester of pregnancy was 1 in 1000 pregnancies (26). Yang et al retrospectively reviewed the maternal and fetal outcomes of 73 single-pregnancies with PROM (16 to 26 weeks).…”
Section: Combination Of Risk Factors Maternal and Neonatal Outcomes mentioning
confidence: 99%
“…Preterm prelabor rupture of membranes (pPROM) is reported to occur in 30–40% of spontaneous preterm births , whereas PROM (prelabor rupture of the membranes at term) occurs in approximately 8% of term pregnancies . Women with PROM are often hospitalized and induced to minimize the risk and pregnancies with pPROM carry a significant risk of perinatal morbidity and mortality . Several risk factors for pPROM have been identified: infection of the genitourinary tract, prior preterm birth, cerclage placement, bleeding, maternal diabetes, cigarette smoking, and Black race .…”
Section: Introductionmentioning
confidence: 99%